2004
DOI: 10.1161/01.atv.0000140198.16664.8e
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Effects of Oral Versus Transdermal Estrogen on Serum Amyloid A (SAA) and High-Density Lipoprotein–SAA in Postmenopausal Women

Abstract: Objectives-Previous studies indicated that oral estrogen increased C-reactive protein by a first-pass hepatic effect. In this study, we determine whether the route of estrogen administration influences serum amyloid A (SAA), another acute-phase protein produced by the liver, and the SAA content of the high-density lipoprotein (HDL-SAA) in postmenopausal women. Methods and Results-In 29 postmenopausal women without coronary heart disease, we conducted a randomized crossover placebo-controlled study to compare e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 28 publications
3
17
0
1
Order By: Relevance
“…Because SAA is conjugated to HDL under pathophysiological conditions [31], we tested whether SAA-HDL also stimulated foam cell formation. Both SAA and HDL-conjugated SAA induced foam cell formation, although SAA-HDL was 40% less efficient (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Because SAA is conjugated to HDL under pathophysiological conditions [31], we tested whether SAA-HDL also stimulated foam cell formation. Both SAA and HDL-conjugated SAA induced foam cell formation, although SAA-HDL was 40% less efficient (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Second, the IUD used by our study women contained levonorgestrel which is an androgenic, testosterone‐derived progestin [28], thus likely to excrete anti‐inflammatory effects analogous to medroxyprogesterone acetate. The mode of action of these hormonal components most probably deals with the first‐pass hepatic effect, as transdermal ERT has an opposite effect on SAA levels compared with oral ERT [25]. However, whether systemic inflammatory reaction is involved in this regulation of SAA is still somewhat uncertain [25, 26] and we were unfortunately unable to evaluate the matter as we did not measure the IL‐6 or TNF‐α levels in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously reported that SAA is conjugated with HDL under pathophysiological conditions (33). To test whether the conjugated SAA also invokes a stimulatory effect on CCL2 production, we first purified apoA-I as described previously (22).…”
Section: Hdl-conjugated Saa Also Stimulates Ccl2 Production In Human mentioning
confidence: 99%